2015
DOI: 10.1152/jn.00348.2014
|View full text |Cite
|
Sign up to set email alerts
|

Retention and interference of learned dexterous manipulation: interaction between multiple sensorimotor processes

Abstract: Fu Q, Santello M. Retention and interference of learned dexterous manipulation: interaction between multiple sensorimotor processes. J Neurophysiol 113: 144 -155, 2015. First published October 1, 2014; doi:10.1152/jn.00348.2014.-An object can be used in multiple contexts, each requiring different hand actions. How the central nervous system builds and maintains memory of such dexterous manipulations remains unclear. We conducted experiments in which human subjects had to learn and recall manipulations perform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 54 publications
0
12
0
Order By: Relevance
“…The partition of learning between the body and the object is consistent with recent advance in object-manipulation studies investigating sensorimotor memory, which was originally referred to as the memory of an object’s physical properties 27 . Researchers have found that memory of previous actions affects object manipulation 13 , 28 , 29 . For instance, after forcefully squeezing an unrelated object people was biased to use a large grip force to lift a familiar object 13 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The partition of learning between the body and the object is consistent with recent advance in object-manipulation studies investigating sensorimotor memory, which was originally referred to as the memory of an object’s physical properties 27 . Researchers have found that memory of previous actions affects object manipulation 13 , 28 , 29 . For instance, after forcefully squeezing an unrelated object people was biased to use a large grip force to lift a familiar object 13 .…”
Section: Discussionmentioning
confidence: 99%
“…We postulate that object learning lasts longer as it is akin to the concept of object permanence 37 39 , while body learning changes more rapidly. Early studies on object grasping have found that people retain the knowledge of weight distribution for more than 24 hours 2 , 40 , while the influence of recent actions only lasts for a brief duration 28 . With accumulating evidence that motor learning consists of components of different time scales 41 43 , our findings suggest that during object manipulation body learning and object learning might be associated with a fast and a slow time scale, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Later studies provided further evidence supporting the concept of multiple sensorimotor mechanisms and how their different time scales may interfere with generalization or retrieval of previously learned manipulation [230]-even when the object being manipulated is the same. A recent study has provided evidence for the co-existence of contextdependent and independent learning processes [204], which would operate similarly to those described for adaptation of reaching movements [231]. The advantage of context-dependent representations of manipulation is that they can be recalled when the object has strong contextual cues (i.e., object geometry and perhaps other perceptual attributes).…”
Section: Learning Vs Implementation Vs Adaptationmentioning
confidence: 81%
“…The fact that the generalized model had the best performance is consistent with the recent trend in neuroscience research, where motor adaptation can be attributed to a combination of parallel neural mechanisms which differ in time-space and sensorimotor memory usage. [5,37,38] In addition, our model can capture within-trial temporal evolution of human motor control during trial-by-trial adaptations, whereas most previous studies consider the motor output and error signals only as scalars for each trial.…”
Section: Discussionmentioning
confidence: 99%